War-to-Peace Transition in Mozambique : The Provincial Reintegration Support Program - World Bank (Washington, DC, 2012)
By mid-1994, nearly a third (5.7 million) of the entire population of Mozambique had been uprooted, either internally displaced or living as refugees in neighboring countries. Rails, roads, and bridges throughout the country were in disrepair. It was estimated that about half of the nation's schools and a third of its health clinics had been damaged or destroyed. Agricultural fields and by-ways had been hardened by drought and were strewn with land mines. Mozambique had become first among the ranks of the world's poorest and aid-dependent nations. When the World Bank initiated its Provincial Reintegration Support Program (PRSP) in July-August 1994, 17 years of civil strife had weakened the social fabric and severely damaged the economic infrastructure of the country. Multi-party democratic national elections, endorsed by both the government and the opposition, took place in October 1994. Thousands of displaced persons returned, spontaneously or with external assistance, to their home villages to put their lives back together again. Amongst these were about 100,000 former combatants being demobilized from active duty. Good rains and the end of the drought resulted in Mozambique's first bountiful harvest in years, setting the stage for social healing, economic stabilization, and a shift from an emergency-reactive focusing on 'saving lives' to a more developmental pro-active mode of promoting 'sustainable livelihood' linked to rehabilitation and reconstruction efforts.